18β-Glycyrrhetinic acid alleviates demyelination by modulating the microglial M1/M2 phenotype in a mouse model of cuprizone-induced demyelination. (11th June 2021) - Tian, Hui; Cheng, Yahong; Zhang, Yiyuan; Bai, Xinying; Jiang, Yuan; Li, Jinjin; Fan, Shiqi; Ding, Hong
Graphical abstract: Highlights: 18β-GA (a constituent of licorice) effectively reversed the mice behavioral dysfunction after exposure to cuprizone for five weeks. 18β-GA sufficiently alleviates demyelination in a mouse model of cuprizone-induced demyelination. The function of 18β-GA is related to moderating M1/M2 polarisation. Abstract: This research aimed to examine the nutritious supplementary function of 18β-Glycyrrhetinic acid (18β-GA) in moderating the myelin sheath destruction and behavioral impairments observed in the cuprizone model of demyelination. Mice were fed daily on food containing cuprizone (0.3 %) and given doses of 18β-GA (5 or 1 mg/kg) for a period of five weeks. The groups treated with 18β-GA exhibited improvements in exploratory behavior, locomotive activity, and weight. As assessed using luxol-fast blue and myelin basic protein (MBP) staining, which were used to detect demyelination in the brain, 18β-GA both reduced and prevented instances of cuprizone-induced demyelinating lesions; treatment with 18β-GA also caused the MBP level in the corpus callosum to increase. Furthermore, alongside these positive results following 18β-GA treatment, microglial polarisation was also observed to shift towards the beneficial M2 phenotype. The results of this research thus indicate the potential clinical application of 18β-GA for the prevention of myelin damage and behavioral dysfunction.